2018
DOI: 10.1142/s0192415x1850026x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Apoptotic Mechanisms of Acupuncture in Neurological Diseases: A Review

Abstract: Apoptosis, known as programmed cell death, plays a significant role in the pathogenesis of neurological diseases. Most of these diseases can be obviously alleviated by means of acupuncture treatment. Current research studies have shown that the efficacy of acupuncture to these medical conditions is closely associated with the anti-apoptotic potentials. Mainly based on the acupuncture's anti-apoptotic efficacy in prevalent neurological disorders, including cerebral ischemia-reperfusion injury, Alzheimer's disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 90 publications
0
20
0
1
Order By: Relevance
“…From the historical perspective, Baihui is the most often-chosen principle acupoint in treating neurological diseases like ischemic stroke and dementia. Nowadays, various basic studies have also confirmed that scalp acupuncture at Baihui plays multiple neuroprotective roles including antiapoptosis, anti-inflammatory, and perfusion augmentation in the pathophysiological process of laboratory models of ischemic stroke, not only regulating oxidative stress [ 24 , 100 102 ]. It has also been reported that acupuncture at Dazhui could enhance the activity of SOD and GSH-Px [ 78 , 92 ], improve perfusion in the ischemic zone, and promote the proliferation of neuronal stem cells [ 101 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the historical perspective, Baihui is the most often-chosen principle acupoint in treating neurological diseases like ischemic stroke and dementia. Nowadays, various basic studies have also confirmed that scalp acupuncture at Baihui plays multiple neuroprotective roles including antiapoptosis, anti-inflammatory, and perfusion augmentation in the pathophysiological process of laboratory models of ischemic stroke, not only regulating oxidative stress [ 24 , 100 102 ]. It has also been reported that acupuncture at Dazhui could enhance the activity of SOD and GSH-Px [ 78 , 92 ], improve perfusion in the ischemic zone, and promote the proliferation of neuronal stem cells [ 101 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Bcl-2 is a tumor suppressor gene which significantly inhibits apoptosis, while Bax is an apoptotic gene which inhibits Bcl-2. It has been reported that the Bcl-2/Bax ratio is a key factor that determines the degree of apoptosis [18]. The results of this study showed that morphine pretreatment significantly raised mRNA levels of p-p38, p-GSK-3β, p-Cx43, Bcl-2 and Bcl-2/Bax, while Bax mRNA levels were decreased.…”
Section: Studiesmentioning
confidence: 46%
“…Later, acupuncture was introduced to other regions, including Asia, Europe, and the United States [ 54 ]. It was proven to be effective for a variety of neurological diseases, including PD [ 6 , 24 ]. PD is a chronic neurodegenerative disease characterized by selective loss of dopaminergic neurons in the substantia nigra, resulting in abnormal motor behavior.…”
Section: Discussionmentioning
confidence: 99%